Pengaruh Strategi B2B Tiktok dan Tokopedia dalam Keputusan Pembelian Barang oleh Konsumen di Lingkungan Mahasiswa - Abdillah, Rizky; Manalu, Bissar; Hotriahman, Toky; Harahap, Ahmad Rizky (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This research aims to analyze the influence of the B2B strategies of TikTok and Tokopedia on purchasing decisions by consumers in the student environment. The results of this research show that the B2B marketing strategy of TikTok and Tokopedia has a significant influence on students' purchasing decisions. The majority of respondents are students aged 18-24 years, the majority of respondents (70%) use TikTok more than 1 hour per day, 85% of respondents have shopped on Tokopedia in the last 3 months. The results of the questionnaire show that 65% of respondents have a positive perception of the marketing strategies implemented by TikTok, especially in terms of creative content and user interaction. On the other hand, 60% of respondents also gave a positive assessment of Tokopedia's marketing strategy, with a focus on ease of access and product variety. SEM analysis shows that there is a significant relationship between perceptions of TikTok's marketing strategy and purchasing decisions on Tokopedia (p 0.05). Apart from that, perceptions of Tokopedia's marketing strategy also have a significant influence on purchasing decisions (p 0.05).